الهيكل الصناعي الدوائي في الجزائر - د. بن بريكة, عبد الوهاب; أ. ميـاح, عـادل (Recherches économiques et managériales, 2011)
الملخص:      إن الهدف من تحليل هيكل الصناعة هو التعرف على الفرص والتهديدات بغية وضع إستراتيجية للمؤسسة تتلاءم مع تلك الصناعة وتنسجم مع أهدافها . وإن تحليل طبيعة الصناعة يساعد على فهم تلك البيئة، وتوفير الدلالات لإستخدام الأساليب الكمية من أجل إتخاذ القرارات الإستراتيجية الملائمة .       حيث أن تحليل الهيكل الصناعي الدوائي في الجزائر يقتضي علينا دراسة التوزيع النسبي للحجم الكلي للصناعة بين المؤسسات المنتجة أي دراسة وتحليل التركز الصناعي، وكذلك تحليل عوائق الدخول إلى السوق الصناعة من قبل المؤسسات الأخرى، لأن بتحليلنا للهيكل الصناعي يمكننا معرفة درجة المنافسة أو الاحتكار في سوق تلك الصناعة، وهذا ما سنحاول توضيحه في هذا المقال   Abstract The aim of analyzing the structure of industry is to identify opportunities and threats in order to develop a strategy for the institution consistent with the industry and consistent with its objectives. The analysis of the nature of the industry helps to understand that environment, and provide indications for the use of quantitative methods in order to take appropriate strategic decisions.       Where the analysis of industrial structure in Algeria requires medical We have to study the relative distribution of the total volume of the industry between enterprises producing any study and analysis of industrial concentration, as well as analysis of barriers to entry to the market industry by other institutions, because our analysis of the industrial structure, we can see the degree of competition or monopoly in the market industry, and this is what we will try to clarify in this article